Black-tufted-ear marmoset Callithrix penicillata (Primates: Callitrichidae) following the army ant Labidus praedator (Formicidae: Ecitoninae) in the Cerrado and the Atlantic Forest, Brazil - Melo Jr., Tadeu Artur; Zara, Fernando José (Neotropical Primates, 2007)
No abstract